Combined Hamartoma of Retina and Retinal Pigment Epithelium Masquerade as Choroidal Melanoma in Young Patient - Amatya, Anupama; Tamang, Saksham; Sthapit, Purnima Rajkarnikar (Nepalese Journal of Ophthalmology, 2026)
Introduction: Combined hamartoma of retina and retinal pigment epithelium is a rare benign ocular tumour resulting from abnormal proliferation of glial cells, vascular tissue and pigment epithelial cells Case: A 29-year-old male presented with complaint of diminution of vision in his right eye, noticed incidentally during screening. Observation: On examination, a flat, unilateral, solitary, greyish brown peri-papillary lesion with irregularly pigmented border with an epiretinal membrane in right eye. The Optical Coherence Tomography showed a thickened retina with disorganisation of retinal layers, a hyper-reflective inner retinal layer with fine retinal traction peaks, and presence of an epiretinal membrane. Histopathological examination was not done. Conclusion: Combined hamartoma of retina and retinal pigment epithelium is a rare benign tumour. Proper diagnosis is important as it can be confused with more severe pathologies like choroidal melanoma, Retinal pigment epithelium adenocarcinoma.